Study of Natural Color Processing in The Creation of Ecoprint Products at UMKM Griya Anyar Dewata - Nadwitya Pramesthi, I Gusti Ayu; Gede Artayani, Ida Ayu (Hastagina : Jurnal Kriya Seni, 2024)
The development of production in textile industry continues to follow current trends, which is fast fashion. Fast fashion is a textile industry that provides the latest fashion that is classified as mass market orientation, namely textile production in large quantities and scales. The fast fashion production process has a negative impact on releasing liquid waste. The waste comes from synthetic colouring which can pollute rivers and domestic waters. People also tend to be consumptive towards inconsistent fashion trends with low fabric quality. This phenomenon is important to further examine for the sake of environmental sustainability. Therefore, this study can be an alternative solution in reducing the impact of synthetic dyes. This study focuses on the processing techniques of natural materials as natural dyes. The technique used in the processing natural materials is ecoprint technique. The result of the application is to create ecoprint products such as bags, scarves, and feysen clothing. The purpose of this study is to provide knowledge and an overview of the processing of natural materials into high-value fashion products that support the concept of sustainable fashion, have great potential of their uniqueness and expected to provide new innovations that produce quality and highly competitive products. The deepening learn of  ecoprint technique uses the active participation method. In line with the internship activities, the active participation method means that in the process of product creation, the author collaborates with partners and expert colleagues who will encourage and take benefit in product creation